2018
DOI: 10.3390/en11081985
|View full text |Cite
|
Sign up to set email alerts
|

Design, Construction, and Testing of a Gasifier-Specific Solid Oxide Fuel Cell System

Abstract: This paper describes the steps involved in the design, construction, and testing of a gasifier-specific solid oxide fuel cell (SOFC) system. The design choices are based on reported thermodynamic simulation results for the entire gasifier- gas cleanup-SOFC system. The constructed SOFC system is tested and the measured parameters are compared with those given by a system simulation. Furthermore, a detailed exergy analysis is performed to determine the components responsible for poor efficiency. It is concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The onboard kerosene fuel is converted to H 2 and CO in the special fuel reformer. Fernandes et al (2018) present the results of studies of design, development, and testing of the SOFC system with a gasifier, which is used as a plasma reactor that processes 8.84 kW of waste. We note the prospects for using plasma technology not only for the gasification of various hydrocarbons but also for organising efficient afterburning of the fuel cell offgases (Gatsenko and Serbin 1995;Matveev et al 2007aMatveev et al , 2015Matveev and Serbin 2012).…”
Section: Intoductionmentioning
confidence: 99%
“…The onboard kerosene fuel is converted to H 2 and CO in the special fuel reformer. Fernandes et al (2018) present the results of studies of design, development, and testing of the SOFC system with a gasifier, which is used as a plasma reactor that processes 8.84 kW of waste. We note the prospects for using plasma technology not only for the gasification of various hydrocarbons but also for organising efficient afterburning of the fuel cell offgases (Gatsenko and Serbin 1995;Matveev et al 2007aMatveev et al , 2015Matveev and Serbin 2012).…”
Section: Intoductionmentioning
confidence: 99%
“…draft gasifier could be a most fitted gasifier for biomass chemical process thanks to inherent blessings like feedstock flexibility, higher method management, low tar formation, and easy to construct. Fernandes et. al.…”
Section: Manuscript Revised June 29 2020 and Published On July 10 2020mentioning
confidence: 99%
“…This Special Issue of Energies on the subject of "Biofuel and Bioenergy Technology" contains the successful invited submissions . A total of twenty-seven technical papers which cover diversified biofuel and bioenergy technology related researches have shown critical results and contributed significant findings in biomass processing [1,2], bio-oil and biodiesel [3][4][5][6][7][8][9][10][11], syngas [12][13][14], biogas/methane [15][16][17][18][19], bioethanol and alcohol-based fuels [20][21][22], solid fuel [23][24][25] and also microbial fuel cell [13,26,27] developments.…”
mentioning
confidence: 99%
“…In addition, it was also found that at higher reaction temperatures, more hydrogen and carbon monoxide were produced. In pilot plant study, the gasifier which was embedded with specific solid oxide fuel cell system in an industrial scale was investigated in details [13]. To further understanding the gasification process, a thermodynamic equilibrium constants derivation and modelling was performed for two cases, with and without tar.…”
mentioning
confidence: 99%